CNS changes in Usher's syndrome with mental disorder: CT, MRI and PET findings. Issue 7 (July 1988) - Koizumi, J; Ofuku, K; Sakuma, K; Shiraishi, H; Iio, M; Nawano, S
Abstract : CNS changes in a case of Usher's syndrome associated with schizophrenia-like mental disorder were observed by CT, MRI and PET. The neuro-radiological findings of the case demonstrate the degenerative and metabolic alterations in various regions of cortex, white matter and subcortical areas in the brain. Mental disorder of the case is almost indistinguishable from that of schizophrenia, but the psychotic feature is regarded as an atypical or mixed organic brain syndrome according to the classification in the third edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM-III).